Unraveling developmental gene regulation in holometabolous insects through comparative transcriptomics and proteomics - Maya Wilkens; Susanne Zimbelmann; Franziska Roth; Jasmin Cartano; Sergi Sayols; Mario Dejung; Michal Levin; Falk Butter (Communications Biology)
Abstract Holometabolous insects undergo complex phenotypic changes during development in four major stages: egg, larva, pupa and adult. Such changes are typically driven by strong transcriptome and proteome dynamics, making this process an excellent system for comparing these two levels of regulation. Here, we provide a comprehensive paired transcriptome and proteome dataset of 17 timepoints across the developmental life cycle of the silkworm Bombyx mori. The analysis of this data revealed similarities and differences between transcriptional and post-transcriptional gene expression, enabling the identification of stage-specific characteristics. Specifically, the oxidative phosphorylation pathway was enriched in genes expressed especially in adults. We examined protein-transcript correlations and characterized stage-specific dynamics. The majority of genes for which transcript and protein dynamics differ are linked to translation and RNA regulation. Our data constitute a rich resource enabling comparative analysis of developmental regulatory dynamics. Comparison of silkworm developmental gene expression with publicly available data for D. melanogaster revealed similar gene regulatory patterns at the transcriptome and proteome levels, underscoring the importance of the evolutionary conservation of tightly coordinated developmental processes.